Implementation of Problem Based Learning Models in Coding and Artificial Intelligence Materials to Train Students's Problem Solving Skills - Nisa, Fairuziyah Aizzatun (Universitas Negeri Makassar, 2025)
The integration of coding and AI learning into junior high school curricula is a strategic initiative aimed at cultivating a competitive young generation that is well-equipped to thrive in the global arena. The ability to solve problems is an essential component of learning coding and AI material. Nevertheless, problem-solving activities in coding and AI materials are still regarded as challenging. The objective of this study is to enhance problem-solving skills by employing the Problem-Based Learning model in coding and AI materials. The present study constitutes a preliminary experimental investigation, employing a one-group pre-test post-test design. The study's participants were 28 seventh-grade students at SMP Negeri 49 Surabaya. This study describes the implementation of learning and students's problem-solving skills. The data collection techniques employed included observation sheets to assess the implementation of learning and problem-solving ability tests. The findings indicated that (1) the mean percentage of learning implementation in the initial meeting was 91.67%, and in the subsequent meeting, it increased to 98.33%, which was considered to be of a very good caliber, and (2) based on the N-gain analysis, the improvement obtained was classified as high with a score of 0.78. The findings of this study demonstrate that the implementation of the PBL model, facilitated by robot simulation and Pictoblox practice, can enhance problem-solving competencies in coding and AI materials.